Correction of tye C atrioventricular canal associated with tetralogy of Fallot. Issue 5 (October 1978) - Bastos, P; De Leval, M; Macartney, F; Stark, J
Abstract : Type C complete atrioventricular canal associated with tetralogy of Fallot in a 5-year old child was successfully corrected. Repair of the atrioventricular canal was combined with infundibular resection and the insertion of an outflow tract patch across the pulmonary valve ring. The postoperative course was uneventful, and the child is well one year after operation.